PELATIHAN PENGGUNAAN BAHAN ALAM PATIKAN KERBAU DAN MADU DALAM PENGENDALIAN Aeromonas hydrophila PADA BUDIDAYA IKAN LELE DI DESA BLEPANAWA - Yuliana Salosso; Bagus Ansani Takwin; Gabriella Augustine Suleman; Tania Nilakandhi; Anggita Noer Laily; Asriati Djonu (Jurnal Abdi Insani, 2026)
Bacterial disease caused by Aeromonas hydrophila is one of the major constraints in catfish aquaculture in Blepanawa Village, East Nusa Tenggara, as it can lead to lesions, reduced survival rates, and fish mortality. The widespread use of antibiotics by farmers poses risks of bacterial resistance and negative environmental impacts; therefore, safer and more sustainable control alternatives are required. This activity aimed to improve farmers’ knowledge and skills in utilizing patikan kerbau (Euphorbia hirta) and honey as natural antibacterial agents. The program was implemented through socialization, training, formulation demonstration, and participatory discussion involving 30 catfish farmers. The results indicated an increase in farmers’ understanding and skills, as reflected by their ability to re-explain the material, prepare the formulation, and independently apply the technique. Farmers also showed positive responses toward the use of natural materials as an alternative disease control strategy. The utilization of patikan kerbau and honey has the potential to support safer, environmentally friendly, and sustainable fish health management through the use of local resources.